Aplikasi Pengunci Alamat Website dan Desktop di Perpustakaan Online Badan Pusat Statistik Provinsi Jawa Barat - Asep Sutisna (LP2M INSTITUT TEKNOLOGI DAN BISNIS ASIA MALANG, 2019)
ABSTRACT. The application for locking the website address and desktop that have been designed at this time can be applied to library computers based on website services (online) in the Integrated Statistics Services (PST) of Statistics (BPS) of Jawa Barat which still uses a web browser without a security application . The disadvantage of using a computer that uses a web browser for a specified website address is that the BPS online library is vulnerable to users who often open a website address other than those that have been specified, change the specified computer settings, and open files that are not allowed. This is because library officers cannot directly monitor users who use the computers. Therefore this application is built so that the computers used for online library can not be easily changed, the user cannot open a website address other than an online library, and the user cannot open files that are not allowed. The system design used in this research journal uses the low fidelity prototype method. The results of testing with the black box method indicate that online library computer users can only open BPS online library application and computer settings can be maintained properly.